Comparing two methods for the identification of news shocks - Paul Beaudry; Franck Portier; Atılım Seymen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Recent empirical literature delivered, based on different structural VAR approaches, controversial results concerning the role of anticipated technology-news-shocks in business cycle fluctuations. We deal with this controversy and investigate (i) the extent to thich two prominent structural VAR approaches can be usefull in recuperating news shock dynamics from artificially generated data in general and (ii) why and to what extent these SVAR approaches differ in the results the deliver in particular. Thereby, we provide several insights for the users of both VAR techniques with small samples in practice.
urn:nbn:de:bsz:180-madoc-353631
Keywords: C32; E32; 330; News Shocks; Structural VAR; Identification